Review of Book on Quality Assurance in Technical Education - Bhattacharya, S. K.; Kulkarni, P. D. (Journal of Engineering Education Transformations, 2005)
This book by Dr S. K. Bhattacharya on "Quality assurance in Technical Education" is written as a reference book for teachers, HODs, principals, state level managers handling Technical Education (TE).